The Chronotope in Space Opera: A Comparative Analysis with the Adventure Novel - Arroyo Barrigüete, Jose Luis (2020)
In this paper we analyze the characteristics of the adventure novel of ordeal, which Bakhtin identifies as one of the three essential types of novelistic unity. The exegesis of such chronotope reveals a pattern not unlike that which articulates a popular sub-genre of science fiction: space opera. Our conclusion is that both chronotopes are virtually identical except for a very relevant aspect, temporal reversibility, absent in space opera, because of a lesser protagonism of the event. This is the result of a heroic axiology that is more typical of the epic than of the novel, an aspect that is also analyzed in the paper.